When Balance Sparks Initiative: Exploring Engagement and Proactive Work Behavior among Employees at Credit Union Semarong Head Office in Sosok - Niranda, Carmelita; Lianto, Lianto (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the influence of work–life balance (WLB) on proactive work behavior (PWB) mediated by employee engagement (EE) among employees at Credit Union Semarong Head Office in Indonesia. Using a quantitative, descriptive-correlation design, data were collected from 49 employees using a structured questionnaire based on validated scales. Data analysis was conducted via Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Results indicate that WLB significantly enhances both EE and PWB, with EE partially mediating the relationship between WLB and PWB. These findings demonstrate that balanced employees possess higher motivation and engagement, which stimulate proactive behaviors. The conclusion affirms the importance of fostering work–life balance and engagement to build resilient, proactive workforces in resource-constrained organizations. This study provides practical and theoretical insights for organizational leaders seeking to promote adaptive and innovative employee conduct.